Epidermal growth factor receptor in breast carcinoma: association between gene copy number and mutations - Lv Ning; Xie Xiaoming; Ge Qidong; Lin Suxia; Wang Xi; Kong Yanan; Shi Hongliu; Xie Xinhua; Wei Weidong (Diagnostic Pathology, 2011)
Abstract Background The epidermal growth factor receptor (EGFR) is an available target of effective anti-EGFR therapy for human breast cancer. The aim of this study was to assess the presence of EGFR gene amplification and mutations in breast cancer and to analyze the association between the statuses of these two gene alterations. Materials and methods EGFR gene amplification and mutations were investigated in formalin-fixed, paraffin-embedded tissues from 139 Chinese female patients with breast cancer by means of fluorescence in-situ hybridization (FISH) and fluorescently labeled real-time quantitative polymerase chain reaction (RT-PCR), respectively. Results EGFR gene amplification was observed in 46/139 (33.1%) of cases by FISH. Based on RT-PCR, 2/139 (1.4%) samples had EGFR gene mutations. Overall, only 1 (0.7%) of the cases was identified with both whole gene amplification and mutation, and 92 (66.2%) of cases were negative for both. High gene copy numbers of EGFR had significant correlation with the occurrence of EGFR protein expressions (P = 0.002). Conclusion In this study, EGFR mutations were presented in only two samples, indicating that EGFR mutations should not be employed in future trials with anti-EGFR therapies for breast cancer. However, EGFR whole gene amplification is frequently observed in patients with breast cancer. It will be of significant interest to investigate whether EGFR gene copy number is a suitable screening test for EGFR-targeted therapy for breast cancer.